Influenza at the 2021 Grand Magal of Touba and possible spread to rural villages in South Senegal - a genomic epidemiological study - Ndiaw Goumballa; Fatou Samba Diouf; Mamadou Beye; Masse Sambou; Hubert Bassène; Mamadou Dieng; Adama Aïdara; Lorlane L.E. Targa; Philippe Colson; Philippe Gautret; Cheikh Sokhna (International Journal of Infectious Diseases, 2024)
Objectives: Influenza is frequent among pilgrims participating in the Grand Magal de Touba (GMT), in Senegal, with a potential to spread to contacts when they return home. Methods: Ill pilgrims consulting at a health care center in Mbacké city close to Touba during the 2021 GMT, pilgrims returning to Dielmo and Ndiop villages, and patients who did not travel to Touba and consulted at health care centers in these two villages in 2021 were tested for the influenza virus by polymerase chain reaction on nasopharyngeal samples. Next-generation sequencing and comparative and phylogenetic analyses of influenza A virus genomes were performed. Results: A total of 62 of 685 patients tested positive for influenza A virus, including 34 of 53 who were consulted in Mbacké in late September, six of 129 pilgrims who returned home in early October, and 20 of 42 villagers from October 3 to 29. A total of 27 genomes were obtained. Four clusters were observed based on the phylogenetic analyses, suggesting that Mbacké patients and returned pilgrims may have shared closely related viral strains with patients inhabiting the villages who did not participate in the GMT. Conclusions: Villagers in Ndiop and Dielmo may have been infected with viral strains originating from the GMT and possibly imported by pilgrims who returned from the GMT.